Three-dimensional localization spectroscopy of individual nuclear spins with sub-Angstrom resolution - J. Zopes (Nature Portfolio, 2018)
Electron spins in nitrogen vacancy centres are perturbed by nearby nuclear spins, making it possible to infer some of the nuclear spins' properties. Here the authors demonstrate a technique that can determine the location of nuclear spins in three-dimensional space using only one electron spin.